Gender and Memory in the Globital Age - Reading, Anna.; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book asks how 21st century technologies such as the Internet, mobile phones and social media are transforming human memory and its relationship to gender. Each epoch brings with it new media technologies that have transformed human memory. Anna Reading examines the ways in which globalised digital cultures are changing the gender of memory and memories of gender through a lively set of original case studies in the 'globital age'. The study analyses imaginaries of gender, memory and technology in utopian literature; it provides an examination of how foetal scanning alters the gendered memories of the human being. Reading draws on original research on women's use of mobile phones to capture and share personal and family memories as well as analysing changes to journalism and gendered memories, focusing on the mobile witnessing of terrorism and state terror. The book concludes with a critical reflection on Anna Reading's work as a playwright mobilising feminist memories as part of a digital theatre project 'Phenomenal Women with Fuel Theatre' which created live and digital memories of inspirational women. The book explains in depth Reading's original concept of digitised and globalised memory - 'globital memory' - and suggests how the scholar may use mobile methodologies to understand how memories travel and change in the globital age. .
Introduction -- PART ONE: Concepts -- 1.Gender, Memory and Technologies -- 2.Globital Memory -- 3.Globital Utopias. Imaginaries of Gender, Memory and Technologies -- PART TWO: Domains -- 4. Globital Body: Birth -- 5.Globital Home: Life -- 6.Globital Publics: Death -- PART THREE: Actions -- 7.Globital Stories -- 8.Epilogue: Gender Recalled.
Keywords: Historiography; Technology in literature; Humanities-Digital libraries; Feminist theory; Memory Studies; Gender Studies